Arabic Vocabulary and Socio-Religious Identity in Indonesian Muslim Society: A Sociolinguistic Literature Review - Khaerul Muttakin; Triani Agustin; Oktavia Dwi Lestari; Abdul Munip; Ninda Maharani; Ahmad Riyadissolihin; Syamsul Wathoni (UIN Salatiga, 2026)
The increasing use of Arabic vocabulary in Indonesian Muslim society reflects a sociolinguistic phenomenon in which language carries not only communicative functions but also social, cultural, and religious meanings. This study aims to synthesize existing scholarship on the role of Arabic vocabulary in the construction of socio-religious identity and to provide an integrated sociolinguistic interpretation through the perspectives of Social Identity Theory and Bourdieu's concept of symbolic capital. This research employed a qualitative approach using a traditional literature review design. Data were collected from peer-reviewed journal articles, academic books, conference proceedings, and other relevant publications published between 2016 and 2026. The collected literature was analyzed thematically by identifying recurring patterns related to identity construction, symbolic meaning, and the social functions of Arabic vocabulary across educational, religious, economic, and public contexts. The synthesis indicates that Arabic lexical practices are consistently interpreted as symbolic resources associated with religious affiliation, identity expression, and the representation of Islamic values across diverse social settings. At the same time, the reviewed literature suggests that these symbolic meanings vary according to educational background, religious orientation, institutional context, and local socio-cultural traditions, indicating that Arabic vocabulary is interpreted differently across Indonesian Muslim communities. The contribution of this study lies in providing a comprehensive conceptual synthesis that integrates findings previously discussed in separate contexts, thereby offering a broader understanding of the dynamic relationship between language, socio-religious identity, and symbolic meaning in contemporary Indonesian Muslim society while identifying the need for further empirical research across diverse local communities.